Mode interactions in photonic crystal nano-cavity arrays - Karim, Efaz; Sabbir, Ehsanul Alam; Shanto, Md. Raisul Islam (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.